Research on relationship between crop drought and soil water retention and supply characters in hilly red clayey soil - LIU Yun-long; LU Jun; WANG Ren-chao (浙江大学学报. 农业与生命科学版, 2002)
This experiment was carried out on quartnary hilly red clayey soil. By measurement of soil water-physical characters and principal soil physical-chemical properties, soil water-holding capacity, soil water release characters and soil water conductivity were analyzed. The results showed that with increase in soil suction, soil water-holding capacity and unsaturated soil water conductivity of paddy soil and upland soil decreased rapidly. Soil water-holding capacity and soil water-supplying capacity of lower soil layers were low compared to surface soil. These factors significantly influenced soil water utilization by crop and substantially contributed to the occurrence of crop drought in hilly red soil.